Keterlibatan Alumni Sekolah Tinggi Pastoral (STP) Dian Mandala Gunungsitoli dalam Kegiatan Hidup Menggereja di Paroki St. Maria Ratu Surga Togizita Nias - Sitepanus Zebua; Kristiana Mendrofa; Nicolaus Halawa (STP Dian Mandala Gunungsitoli Nias Keuskupan Sibolga, 2025)
This research was motivated by concern about the low awareness of some alumni of STP Dian Mandala Gunungsitoli in living Missio Canonica, which is part of their responsibility of ministry. The main focus of this research is to analyze the level of alumni involvement in church life, particularly in St. Maria Ratu Surga Togizita Parish, with the aim of obtaining a clear picture of their role in liturgical, catechetical, and pastoral activities. The approach used was qualitative with a case study method that allowed the researcher to explore the experiences and dynamics of alumni ministry among the congregation. Data were collected through direct observation in the parish, in-depth interviews with ten informants consisting of the parish priest, pastoral council administrators, and active members of the congregation, and also through documentation of relevant activities. The results of the study show a striking difference in alumni involvement; those who live in the parish center tend to be more active participants in various church activities, while alumni who domiciled in the station showed lower participation. Factors influencing these differences include busy work, limited follow-up development after the study period, and minimal communication with the parish. These findings provide important evaluations for STP to focus more on long-term alumni development, while also providing input for local churches to design more effective mentoring strategies. Furthermore, this study reminds alumni to reflect on their calling to ministry and live it out in their daily lives.